Piloting the Extension for Community Healthcare Outcomes (ECHO) Pediatric Oncology Telehealth Education Program in Western Kenya: Implementation Study - Tyler Severance; Gilbert Olbara; Festus Njuguna; Martha Kipng'etich; Sandra Lang'at; Maureen Kugo; Jesse Lemmen; Marjorie Treff; Patrick Loehrer; Terry Vik (JMIR Formative Research)
Abstract BackgroundChildhood cancer has an annual incidence of 150‐160 cases per million children worldwide but remains vastly underdiagnosed in low- to middle-income countries such as those in Sub-Saharan Africa. The Moi Teaching and Referral Hospital (MTRH) serves a population of 25 million people, including 10 million children. The average number of pediatric cancer diagnoses was 216 cases annually in 2017‐2019, which was well below the anticipated 1500 cases based on epidemiology data. The remaining 75%‐80% of pediatric cancer cases remain undiagnosed, and these patients are not likely to survive. Prior outreach and needs assessments demonstrated a lack of medical knowledge related to pediatric cancer as a primary barrier to improved referrals, diagnoses, and ultimately, cure. ObjectiveThis study aimed to address disparities in medical knowledge contributing to low diagnostic rates of cancer in children. We implemented Project ECHO (Extension for Community Healthcare Outcomes)—a validated virtual guided practice and telementoring model—to connect multidisciplinary specialists at MTRH with staff in medically underserved communities in western Kenya for training, technical assistance, and mentorship. MethodsSessions were freely available on Zoom twice monthly and featured an expert-led didactic topic followed by a learner-led, case-based discussion. The discussion used dialogue education to promote learning and engagement among participants, with mentorship from the expert team. Information on ECHO participation was tracked, and electronic surveys were sent to the participants at the end of the pilot year. The ECHO program was run in parallel with the pediatric oncology cancer registry to monitor trends in diagnostic rates within the referral region. ResultsThe ECHO program launched successfully in January 2020 with a curriculum focused on pediatric oncology for health care providers. A total of 22 sessions were conducted, with an average of 23 learners per session. A total of 148 participants attended at least one session, with the majority (n=80, 54.1%) attending multiple sessions. The year-end analysis in January 2021 demonstrated that 286 new pediatric patients were diagnosed with cancer at MTRH, representing a 33% increase over the 3-year average. ConclusionsThe Project ECHO platform created a dynamic virtual platform to continue to engage stakeholders across western Kenya. The implementation of this telehealth education platform in Kenya represents an effective model for increasing the recognition and earlier referral of childhood cancer in low- to middle-income countries.